The Leader of the Band: A Case Story of Community Music Therapy on a Hospital Ward for People Who Have Dementia - Patrice Dennis; Daphne Joan Rickson (Voices, 2014)
This case story was undertaken as part of a research project[1] investigating music therapy to aid relationships between people with dementia and their family members. Involving family members in the music therapy process was found to be valuable in fostering a sense of community between residents, family members, and care staff (Dennis, 2012). However, a sense of community was also fostered by the interactions of the residents themselves as they participated in music therapy over a ten month period. Music making became a natural part of the environment, an important medium for individual expression, shared communication, enhancing social events, and demonstrating mutual care and love. We demonstrate this through our case story of Jack[2] whose music making permeated the dementia ward to invite the active participation of others, and led to the development of caring relationships.